Dentoskeletal effects of the maxillary splint headgear in the early correction of Class II malocclusion - José Augusto M. Miguel; Caterina Masucci; Luciana Quintanilha Pires Fernandes; Flavia Artese; Lorenzo Franchi; Veronica Giuntini (SpringerOpen, 2020)
Abstract Background To compare dentoskeletal changes produced by the maxillary splint headgear and cervical headgear appliance during the early phase of Class II treatment, specially the initial overjet and upper incisors position. Subjects and methods In this retrospective study, 28 Class II patients treated with the maxillary splint headgear (MSG, mean age 10.1 ± 1.9 years) and 28 Class II patients treated with cervical headgear (CHG, mean age 9.5 ± 1.9 years) were evaluated before and after treatment. Statistical comparisons between the two groups for cephalometric measurements at T1 and for T2-T1 changes were performed by means of independent sample t tests. Results The MSG showed a significantly greater reduction of the overjet in comparison to the CHG (− 2.4 mm and − 0.7 mm, respectively) and a significantly greater maxillary incisor uprighting (− 1.8 mm and 0.4 mm, respectively). In the MSG, overjet correction was due mainly to mandibular advancement (3.5 mm), while the correction of molar relationship (3.9 mm) was 64% skeletal and 36% dentoalveolar. In the CHG, the overjet correction was also more skeletal, due to mandibular growth (1.8 mm), while correction of molar relationship (3.5 mm) was 63% dentoalveolar and 37% skeletal. Conclusions Both groups showed favorable skeletal mandibular changes, which was more significant in the MSG. Regarding tooth movement, the maxillary splint headgear was more effective in uprighting upper incisors and reducing the overjet than cervical headgear appliance.